1981
DOI: 10.1097/00000658-198110000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism

Abstract: Thirty-nine patients with primary hyperparathyroidism were studied four to eight years after their initial operation. In six patients, both the pathologist and surgeon agreed on the diagnosis of solitary adenoma; in 16 patients, the surgeon diagnosed solitary adenoma and the pathologist parathyroid hyperplasia (microscopic hyperplasia). In 16 patients, primary chief cell hyperplasia was agreed upon by the pathologist and surgeon. In the 16 patients with microscopic hyperplasia, there have been no long-term rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Microscopic hyperplasia was previously demonstrated in the remaining parathyroid glands after surgery for a single adenoma [16]. Thus the possibility of persistent HPT as a cause of the elevated postoperative PTH levels must be considered.…”
Section: Persistent Hpt/parathyroid Functionmentioning
confidence: 95%
“…Microscopic hyperplasia was previously demonstrated in the remaining parathyroid glands after surgery for a single adenoma [16]. Thus the possibility of persistent HPT as a cause of the elevated postoperative PTH levels must be considered.…”
Section: Persistent Hpt/parathyroid Functionmentioning
confidence: 95%
“…In addition, some groups have reported that microscopically hyperplastic glands of normal size are of no clinical significance and that the removal of such glands is unnecessary [ 23 ]. After experienced surgeons inspected ambiguous parathyroid lesions in patients with MGD and double adenoma, they decided whether a frozen biopsy should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, intraoperative PTH monitoring is thought to confuse the decision-making process [ 27 30 ]. Furthermore, undetected hyperplastic glands of normal size in the preoperative imaging study are of no clinical significance, and the removal of such glands is unnecessary [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involved parathyroid cells express more or less distinct phenotypic abnormalities in support of the association of morphology and function [5], which includes such functional characteristics as calcium receptor expression and parathyroid hormone immunoreactivity [6 -8]. Microscopic foci of morphologically abnormal parathyroid cells nevertheless must be assumed to be consistent with the absence of a clinically overt parathyroid disorder [9,10].…”
mentioning
confidence: 99%